PENERAPAN TATA KELOLA YANG BAIK DI NEGARA BERKEMBANG STUDI KASUS RWANDA, BRAZIL, DAN BOTSWANA - Hidayatullah, Mahdi (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2024)
This study aims to evaluate the implementation of good governance in developing countries through the Systematic Literature Review (SLR) approach. Good governance, which includes transparency, accountability, community participation, and political stability, is a key element in creating effective and competitive governance. The results of the review show that the implementation of good governance in developing countries still faces various challenges, such as weak law enforcement, high levels of corruption, and lack of technological infrastructure and community participation. However, several countries, such as Rwanda, Brazil, and Botswana, have shown success in implementing innovative governance reforms through the use of digital technology and e-governance, fiscal decentralization, and the strengthening of anti-corruption institutions. This research also highlights the importance of political stability in supporting the implementation of effective governance. Countries with high political stability tend to be more successful in implementing governance reforms than countries with political instability. This study provides recommendations to strengthen governance in developing countries through increased transparency, accountability, and use of technology, as well as strengthening supervisory institutions and public participation. In addition, a strong political commitment is needed to ensure the sustainability of governance reforms in these countries.